Atrial flutter in a patient with left isomerism and left-sided inferior vena cava interruption - Soto, Richard (2016)
We report the ablation of an atrial flutter with a 260 ms cycle length in a 28-year-old patient with left isomerism and interrupted left inferior vena cava. We showed the participation of the suprahepatic – tricuspid isthmus in the macro reentry circuit by the entrainment maneuver.